POLITICAL COMMUNICATION AND VOTER RESPONSE FRAMEWORK IN GARUT FOR THE 2024 REGIONAL ELECTION - Adnan, Iis Zilfah; Fadhlurrohman, Mochammad Iqbal; Adnan, Zulkifli; Fauzan, Hasbi Shiddiq (Universitas Negeri Semarang, 2025)
This study analyzes the dynamics of political communication and voter responses in the 2024 Garut regional election by highlighting differences in campaign strategies, the role of the media, and the influence of local institutions. Drawing on political communication theory—including agenda setting, framing, political storytelling, and populist communication—and a neo-institutionalist approach, this study explains how formal and informal institutions shape the effectiveness of political messages. Using media content analysis, digital discourse analysis, word network visualization, and in-depth interviews, the study finds that the Helmi–Yudi ticket emphasizes an image of experience and stability, while the Syakur–Putri ticket prioritizes a narrative of change through populist and digital strategies. Social media remains a dominant arena in shaping public opinion, while Garut's socio-religious structure continues to influence voter preferences. This research contributes to the development of a model that integrates political communication and neo-institutionalism, while enriching the study of voter behavior at the local level.